BANTUAN PANGAN NON TUNAI (BPNT) PADA KELUARGA PENERIMA MANFAAT (KPM) DI DESA BALAM MERAH, KECAMATAN BUNUT, KABUPATEN PELALAWAN - Khoryani, Mifta; ', Risdayati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This research entitled “Non Cash Food Assistance Program (BPNT) For Beneficiary Families (KPM) In Balam Merah Village, Bunut District, Pelalawan Regency”. This study aims to determine the impact of the assistance program on the social walfare of beneficiary families (KPM). The problem examined in this study are: (1) How is the implementation of non cash food assistence (2) what is the impact of non cash food assistance on walfare. The method used in this research is quantitative research. Data collection techniques in this study in the form observation, guided interviews, and documentation. The population totaled 190 people and the sample in this study was calculated using the slovin formula, then the results were obtained with a total of 66 people. And the results of research show that the implementation of non cash food assistence (BPNT) consisting of 6T was in the good category. The impact of non cash food assistance on welfare is a positive impact is also in the moderate category. Keyword: Welfare, Non Cash Food Assistence